Developing Liveworksheets as Interactive Instructional Media for Teaching Reading Report Text at Grade X - Amanda Eka Suci An Nisa; Indah Tri Purwanti; Hadriana (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
Instructional media plays a crucial role in engaging students, especially in English language learning. This research aimed to develop and validate interactive instructional media using Liveworksheets for Teaching Reading Report Text to Grade X students. This development research employed the ADDIE model, encompassing Analyze, Design, Develop, and Validation phases. Need analysis was conducted through interviewing three English teachers, distributing questionnaires to 55 Grade X students, and analyzing documents. The student questionnaire results showed that 90.9% of them struggled with report text comprehension, primarily due to unfamiliar vocabulary (60%) and difficulties in identifying the social function (41.8%). Despite these difficulties, 96.4% of students preferred technology-based learning. These findings served as the empirical basis for developing interactive Liveworksheets media. The three experts validated scores of 3.52 for content, 4.00 for instructional media, and 4.00 for pedagogical aspects, all categorized as "Very Valid." Furthermore, a practicality evaluation involving 20 students of grade X showed positive responses, with students finding the media engaging and easy to use. The conclusions confirm that the developed media is pedagogically sound, technically functional, and aligned with the Merdeka Curriculum's emphasis on technology integration and student-centered learning. This research contributes to digital instructional media development for English language teaching in Indonesian secondary schools, particularly to enhance reading comprehension of factual texts.